Agricultural roles in landscapes y taskcapes: An interdisciplinary approach from Northwestern Argentina - Korstanje, María Alejandra (2015)
Traditionally, the agriculture of Argentina's Formative Period (1000 BC - 1000 AD) has been conceived as technologically simple and spatially reduced. However, this simplicity must be reconsidered when we take into account that these technologies made it possible for millennia to practice agriculture in desert environments with eroded and underdeveloped soils. Our research in El Bolsón valley, which is a high basin in western Catamarca province in Argentina, has allowed us gain a detailed understanding of certain farming practices in relation to irrigation technologies, field preparation, and other agronomic techniques, as well as to determine how the agrarian landscapes were structured in the past. In this presentation we summarize the results obtained through multiple lines of research (including landscape archeology and archaeobotany), which now allows us to discuss ideas about agriculture as perpetuated by traditional models, and also to rethink these from a perspective that considers the complexity of the relationships among plants, soil, water, agricultural knowledge, and ways of organizing labor. We have been able to recognize a significant variability of the farming practices through which agriculture was configured during the Formative period. We have also recognized the persistence of certain aspects of this agriculture during the Regional Development Period (1000 - 1500 AD), for which a re-articulation of production and power structures has been assumed.